The Antecedent of Consumer Attitudes Toward Online Shopping in Beauty Industry: The Role of Trust as mediating - Dwike, Marietta (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
—This study to investigate the mediating effect of Trust in the relationship between RelativeAdvantage, Electronic Word of Mouth on Consumer Attitudes Toward Online Shopping in the BeautyIndustry. The respondents are 290 people from beauty Xyz customers. The design research used a surveymodel purposive sampling method as a sampling technique. The data analysis in this research usedStructural Equation Modeling (SEM) as an analysis technique with AMOS as an analysis tool. The resultsshow that Relative Advantage and Electronic Word of Mouth is not statistically significant impactconsumer Attitudes Toward Online Shopping; the results confirm that Trust mediates the effects ofRelative Advantage on Attitudes Toward Online Shopping.